Prevalence of menstrual disturbances among female students of fourth and fifth classes of curative medicine faculty (KUMS) - Aram Aber, Prof. Doctor Fahima (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
In a normal condition, menstrual cycle days are 21-34 days with 80cc normal bleeding and alterations from these parameters are called menstrual disturbances or problems.Goal: The main objective of this research was prevalence of menstrual disturbances among students of fourth and fifth classes of curative medicine faculty (KUMS).Method: This study employed a descriptive cross-sectional design. It was done during 3 months (September, October and November of 2017) in Obstetric & Gynecology Department. Participants were from fourth and fifth classes of curative medicine faculty (KUMS).Results: A total of 86 female students from fourth and fifth classes of curative medicine faculty (KUMS) participated in this research. The mean age of study participants was 22.71 1.0066 ( SD) years with a range of 21-25 years age. The prevalence of menstrual disturbance was 84.88%. The peak of incidence (80.82%) was during ages less than 23 years. Students with early menarche (11-13 years) had a greater percentage (56.16%). The majority of students (71.23%) had 5-7 days menstruation and students with 21-30 days menstruation cycle were at a greater risk of menstrual disturbances (71.23%).In 79.45% of cases, participants had regular menstrual cycle and only 20.54% had irregular menstrual cycle. Overall, hypermenorrhea was prevalent in 32.87%, Oligo-menorrhea in 31.50%, hypo-menorrhea in 23.28%, poly-menorrhea in 20.54%, meno-metrorrhagia in 8.21% and menorrhagia and metrorrhagia in 10.95%.Conclusion: This study has shown that menstrual disturbances are highly prevalent (84.88%) in students with 21-25 years of age, and in the most cases, hyper-menorrhea was dominantly prevalent in female students. Considering the high prevalence of menstrual disturbances, we could give them a better life experience, diagnosing and treating it earlier and increase their content and quality of life during the youth.